Nesting Island Creation for Wading Birds - C. Leann White; Peter C. Frederick; Martin B. Main; James A. Rodgers, Jr. (EDIS)
Many long-legged wading birds such as little blue herons (Egretta caerulea), great blue herons (Ardea herodius), and great egrets (Ardea albus) nest together in large aggregations called breeding colonies. Although different species vary in their habitat preferences, wading birds have several common requirements for nesting. Colony sites must provide protection from predators, nesting materials, and nearby foraging areas (Hafner 2000). In the past, wading birds nested in natural wetland habitats that are becoming increasingly scarce as wetland habitats are continually altered or degraded to accommodate human needs. The future success of wading bird populations may be determined by how well they cope with manipulated foraging and nesting habitats. In this document, we make recommendations on the creation of nesting islands for long-legged wading birds.  This document is CIR1473, one of a series of the Wildlife Ecology and Conservation Department, UF/IFAS Extension. Original publication date May 2005. Minor revision September 2008.